2006
DOI: 10.1080/00150190600716978
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of La-Doped PBN Ferroelectric Ceramics

Abstract: In this work, pure and La 3+ -doped PBN56 ceramics (La 3+ added from 0 wt% to 4 wt%) were fabricated and studied concerning its structure, microstructure and dielectric properties. The analysis of the microstructure of the ceramics showed a change of the grain morphology for ceramics with La content higher than 1.0 wt%. X-ray diffraction and Raman spectroscopy were performed to study the structure of the PBN56 ceramics. The results showed the presence of an orthorhombic phase, whose concentration is increased … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
7
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 11 publications
2
7
0
Order By: Relevance
“…La 3+ -modified PBN ferroelectric ceramics were characterized for microstructure and dielectric properties. The microstructural analysis exhibited a change in the grain morphology and the results confirmed the presence of orthorhombic phase, and increasing La 3+ enhanced the orthorhombicity [9]. Phase evaluation and densification behaviour of PBN ceramics at (1 − x) = 0.7, 0.6 and 0.5 have been reported by Carmo et al [10].…”
Section: Introductionsupporting
confidence: 71%
See 1 more Smart Citation
“…La 3+ -modified PBN ferroelectric ceramics were characterized for microstructure and dielectric properties. The microstructural analysis exhibited a change in the grain morphology and the results confirmed the presence of orthorhombic phase, and increasing La 3+ enhanced the orthorhombicity [9]. Phase evaluation and densification behaviour of PBN ceramics at (1 − x) = 0.7, 0.6 and 0.5 have been reported by Carmo et al [10].…”
Section: Introductionsupporting
confidence: 71%
“…It is well known that the larger tolerance factor and electronegativity difference are in favour of stabilizing the tungsten bronze phase [22]. As Ce concentration increased from undoped to 6 mol% in PBN, the lattice parameters a and c increased up to 6 mol% and further increment of Ce [9]. The theoretical density and experimental density of Cemodified lead barium niobate ceramics is represented in Fig.…”
Section: Resultsmentioning
confidence: 98%
“…The doping of La 3 þ ions can modify the morphology of grains and Curie temperature of the PN-based ceramics [7]. The Ca 2 þ , Mn 4 þ and Ti 4 þ ions were also found to facilitate the densification of the PN-based ceramics [8][9][10].…”
Section: Introductionmentioning
confidence: 97%
“…Venet et al found that the incorporation of La 3þ into the PN-based ceramics can change morphology of grains and Curie temperature [5]. The adding of Mn 4þ and Ca 2þ is also in favor of fabricating dense PN-based ceramics with good piezoelectric properties [6].…”
Section: Introductionmentioning
confidence: 98%